ABDULAHAD NURİ VE DİVANIN TENKİTLİ METNİ - ÇELİK, NİLÜFER (Fırat Üniveristesi, 1999)
Yüksek Lisans Tezi ABDULAHAD NURİ VE DİVANININ TENKİTLİ METNİ Nilüfer ÇELİK Fırat Üniversitesi Sosyal Bilimler Enstitüsü Türk Dili ve Edebiyatı AnabilimDalı Sayfa: 162 Abdulahad Nuri, 17.y.y.'da yaşamış mutasavvıf bir şairdir. Sanatı ikinci

SUMMARY High Bachetor's Degree Thesis ABDULAHAD NURI'S DIVAN AND FIXED TEXT Nilüfer ÇELİK Fırat University The institute of Social Sciences Department Of Türk Language And Litereatve Page: 162 Abdulahad Nuri who lived in the 17 th Century is a mystic writer. In; his art became a matter of secondary importance for him and used his poems for giving recommendation. Abdulahad Nuri used, appoxi mately, every kind of verse in his poems and benefitted from classical ottomon poetry and controlled meter, poetry, in general. He also used rhyme, and semi-rhyme in his poems as an accord. In his social life he used a plain language, a short combination and idioms in his poems. By using some old Turkish words and expressions he contituted his divan. As a result Abdullahiid Nuri' s divan and fixed text has been formed and translated into the new language. Keeping in mind his divan, Abdulahad Nuri's life, his literary personality has been brought up and owing to this,'his place has been determined among the other old Turkish literature writers. Key Words: Mystic, Abdulahad Nuri
Abdulahad Nuri's divan and fixed text
Keywords: Türk Dili ve Edebiyatı; Turkish Language and Literature